Illegal music downloads : understanding why Singaporeans are still doing it. - Siti Norasikin Ahmad. (2010)
Singapore has earned a reputation as being a safe, low crime country, where laws are firmly enforced and intellectual copyrights are protected. According to a recent survey though, more than half a million Internet users in Singapore regularly download music online ?with a majority reporting that they have done so illegally. It is therefore somewhat surprising that many thousands of Singaporean Internet users are still actively involved in downloading music illegally. With the birth of MP3 blogs, where sharing music files is made even easier and safer, the number of people engaging in such activities is rising. In Singapore, like most countries worldwide, it is a criminal offence to download music illegally. Thus, the research question being asked in this paper is simply "why are Singaporeans still participating in illegal music downloads"?This pilot study reports results of an online survey exploring the rationale behind Singaporeans' interest in and willingness to download music online illegally.